Eicosapentaenoic Acid Supplementation Changes Fatty Acid Composition and Corrects Endothelial Dysfunction in Hyperlipidemic Patients. (26th December 2012) - Yamakawa, Ken; Shimabukuro, Michio; Higa, Namio; Asahi, Tomohiro; Ohba, Kageyuki; Arasaki, Osamu; Higa, Moritake; Oshiro, Yoshito; Yoshida, Hisashi; Higa, Tohru; Saito, Taro; Ueda, Shinichiro; et al.
Abstract : We investigated the effects of purified eicosapentaenoic acid (EPA) on vascular endothelial function and free fatty acid composition in Japanese hyperlipidemic subjects. In subjects with hyperlipidemia (total cholesterol ≥ 220  mg/dL and/or triglycerides ≥ 150  mg/dL), lipid profile and forearm blood flow (FBF) during reactive hyperemia were determined before and 3 months after supplementation with 1800 mg/day EPA. Peak FBF during reactive hyperemia was lower in the hyperlipidemic group than the normolipidemic group. EPA supplementation did not change serum levels of total, HDL, or LDL cholesterol, apolipoproteins, remnant-like particle (RLP) cholesterol, RLP triglycerides, or malondialdehyde-modified LDL cholesterol. EPA supplementation did not change total free fatty acid levels in serum, but changed the fatty acid composition, with increased EPA and decreased linoleic acid, γ -linolenic acid, and dihomo- γ -linolenic acid. EPA supplementation recovered peak FBF after 3 months. Peak FBF recovery was correlated positively with EPA and EPA/arachidonic acid levels and correlated inversely with dihomo- γ -linolenic acid. EPA supplementation restores endothelium-dependent vasodilatation in hyperlipidemic patients despite having no effect on serum cholesterol and triglyceride patterns. These results suggest that EPA supplementation may improve vascular function at least partly via changes in fatty acid composition.